Investigating the enhanced kinetics of LiNi0.08Mn1.92O4 cathode material by regulating calcination temperature for long life lithium-ion battery. (December 2018) - Lu, Yao; Luo, Xueying; Bai, Hongli; Guo, Junming; Xiang, Mingwu; Su, Changwei; Liu, Xiaofang; Bai, Wei; Wang, Rui
Abstract: Various LiNi0.08 Mn1.92 O4 cathode materials were prepared by a solution combustion method at 500 °C for 1 h combined with two-stage calcination at 600, 650, 700, and 750 °C for 3 h, respectively. Systematic characterization and test approaches were carried out to investigate the effect of calcination temperature on the crystal structure, morphology, electrochemical performance and kinetics properties of the as-obtained LiNi0.08 Mn1.92 O4 samples. As a result, all the LiNi0.08 Mn1.92 O4 samples show the intrinsic spinel phase with a good crystallinity. The particles size increases with the increased calcination temperature. Especially, the LiNi0.08 Mn1.92 O4 sample prepared at 700 °C (LNMO-700) has a great Li + ion diffusion coefficient and a low apparent activation energy, resulting in an enhanced kinetics. Owing to these merits, the optimized LNMO-700 cathode material exhibits a high initial discharge capacity of 105.0 mAh g −1 and improved retention of 68.6% after 1000 cycles at 1 C, whilst delivers a good rate capability of 95.7 mAh g −1 at a high current rate of 5 C. Highlights: The spinel LiNi0.08 Mn1.92 O4 cathode material has been rapidly prepared by a solution combustion method. Diffusion coefficient and apparent activation energy of the LiNi0.08 Mn1.92 O4 cathode material were calculated and discussed. Enhanced kinetics by regulating calcination temperature.